Gênero relato de experiência de vida: enfoque na modalidade EJA - Lima, Antonia Elizabeth de (2019)
This research project was realized in the educational establishment Centro Estadual de Educação Básica para Jovens e Adultos - CEEBJA, in the city of Toledo/PR. The participants of the research were young and adult students, with ages between 17 and 47 years old, mostly laborers, inserted in drugs or food factories from the city of Toledo/PR, while other are workers from the rural zone, in the context of agribusiness. The research about Portuguese Language teaching-learning considered the language as a way of interaction between subjects, this way, it was possible to deal with reading and teaching from a socio-cognitive and interactionist perspective, following Marcuschi (2008) guidelines. We tried to work the text as a result of a linguistic action with links related to the world. The texts are present in all the daily activities and work as reflection instruments about the various actions practiced by social subjects. The written production considered the observation of EJA students’ difficulties to deal with written texts, to keep a dialogue between texts and to relate information from various texts that they are in contact with. The general objective of this research was to develop reading and writing activity from the contact of the student with diverse textual genre, from a proposal in which the student could perceive and understand the intertextuality as a phenomenon present in various texts and be able to deal with explicit and implicit intertextuality in the text. We also considered the presence of implicit and/or explicit intertextuality in the texts used in class, as well as lead the student to recognize and analyze the implicit and/or explicit intertextuality in the genre life experience report. In this perspective, the students developed the ability to write and understood the discourse of different texts that they had contact with. This way, they could verify how the intertextual relation occurs. In this sense, we believe that the texts produced portray significative advances in the language learning-teaching as constitutive part in the historical and social formation of students inserted in EJA modality.